O'Sullivan stew : a tale cooked up in Ireland - Talbott, Hudson (Putnam's, 1999)
When the witch of Crookhaven, a village on the zigzagging coast of Ireland, has her horse stolen by the King and strikes back with famine and disaster, Kate decides to save the day by getting the horse back for her.